LEGAL ANALYSIS OF THE REVERSE BURDEN OF PROOF IN CORRUPTION CASES - M. Ridho; Mhd Azhali Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Corruption is an extraordinary crime that has a systemic impact on state finances and the social order of society. In an effort to eradicate corruption, Indonesia has implemented a limited and balanced reverse burden of proof system as stipulated in Articles 37 and 37A of Law Number 20 of 2001. This system shifts part of the burden of proof from the public prosecutor to the defendant, who is required to prove the origin of wealth that is not balanced with his income. Although this system is effective in accelerating the judicial process, recovering state losses, and providing a deterrent effect, its implementation faces challenges such as limited competence of law enforcers, potential human rights violations, and limited supporting infrastructure. This study uses normative legal methods with a statutory and conceptual approach to analyze the effectiveness of the implementation of the reverse burden of proof system in corruption crimes. The results of the study indicate that this system requires regulatory harmonization, strengthening the capacity of law enforcement, and developing supporting technology to ensure its implementation runs optimally. Recommendations submitted include intensive training for law enforcers, the preparation of clear technical guidelines, and increasing international cooperation to track and recover hidden assets. With these steps, the reverse burden of proof system can be an effective instrument in eradicating corruption without neglecting the principles of justice and protection of human rights.